2014
DOI: 10.4236/ijohns.2014.35053
|View full text |Cite
|
Sign up to set email alerts
|

Endocranial Complications of Endoscopic Sinus Surgery: Learning from Experience

Abstract: Objectives: We critically reviewed our experiences in endocranial complications with Functional Endoscopic Sinus Surgery, and investigated the causes, prevention strategies and management. Methods: We conducted a retrospective study of endocranial complications with Functional Endoscopic Sinus Surgery performed during last 10 years in our ENT department. We analyzed endocranial complications, their causes, consequences, treatments and outcomes. Management was performed in collaboration with neurosurgeons and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The intracranial complications included 14 CSF leaks, 3 direct frontal lobe injuries, 1 incident of subarachnoid hemorrhage, 2 cases of meningitis, and 3 cases of pneumocephalus. Pneumocephalus is a rare neurological complication of ESS, and other than those reviews 1362,1363 previously described, other case reports 1364,1365 of pneumocephalus after ESS seem to imply that this complication is sufficiently managed with endoscopic closure. 1366 Microdebriders or tissue shavers have revolutionized the manner in which ESS is performed.…”
Section: S169mentioning
confidence: 96%
See 1 more Smart Citation
“…The intracranial complications included 14 CSF leaks, 3 direct frontal lobe injuries, 1 incident of subarachnoid hemorrhage, 2 cases of meningitis, and 3 cases of pneumocephalus. Pneumocephalus is a rare neurological complication of ESS, and other than those reviews 1362,1363 previously described, other case reports 1364,1365 of pneumocephalus after ESS seem to imply that this complication is sufficiently managed with endoscopic closure. 1366 Microdebriders or tissue shavers have revolutionized the manner in which ESS is performed.…”
Section: S169mentioning
confidence: 96%
“…Armengot-Carcellar et al 1362 reported a 0.39% incidence of intracranial complications in 763 patients; 3 patients developed CSF rhinorrhea, 1 of which developed a brain abscess requiring incision and drainage. Hou et al 1363 reviewed their series of ESS and found 19 cases of intracranial complications.…”
Section: S169mentioning
confidence: 99%